STUDI PERBANDINGAN PENGAMALAN KARAKTER PATRIOTISME ANTARA ETNIS MELAYU DENGANETNIS TIONGHOA SISWA SMAS MAHA BODHI KABUPATEN KARIMUN - Ramona Saputri Saputri; Hambali '; Gimin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT:The background problem of this research was because of there is difference between Malay ethnic students and Chinese ethnic students toward the implementation of patriotism characteristic in SMAS Maha Bodhi Karimun Regency. In this research, the formulation of the problem was come from the idea that there is the difference in implementing the patriotism characteristic between Malay ethnic students and Chinese ethnic students of SMAS Maha Bodhi Karimun Regency. Furthermore, the aimed of this research was to find out the difference in implementing the patriotism characteristic between Malay ethnic and Chinese ethnic students. The participants of this research were 7 students who come from Malay ethnic and 52 students of Chinese ethnic. This research used an instrument which content of 27 questions. This research was analyzed using “t” test. This finding research was found that the students from Malay ethnic got the average score about 71,29 % while the students from Chinese ethnic got the average score about 68,56 %. From this finding, we can conclude that there is no significant difference between Malay ethnic and Chinese ethnic students in implementing the patriotism characteristic of SMAS Maha Bodhi Karimun Regency. Keyword : implementing, patriotism characteristic